AB0865 Serum urate and its association with race in young adults: baseline analysis from a randomized clinical trial. (15th June 2017) - Saddekni, MB; Gaffo, AL; Foster, PJ; Biggers, SR; Rahn, EJ; Li, P; Saag, KG
Abstract : Background: Increased levels of serum urate (sUA) have been reported in association with hypertension, chronic kidney disease and obesity. All these conditions are over-represented in US African Americans, who also have greater environmental risk factors for hyperuricemia development including elevated fructose intake. Our group has previously reported that young African Americans have lower sUA concentrations than Caucasians after adjustment for clinical and demographic factors. Objectives: To determine whether there is a differential association between sUA and race in young adults. Methods: We examined baseline data on consecutively enrolled individuals (age 18 – 40 years) in an interventional study aimed at lower blood pressure (BP) through the administration of urate-lowering therapy. African Americans were over-represented in the sample by study-design. Inclusion criteria included a sUA of ≥5.0 mg/dL for men or ≥4.0 mg/dL for women. After means comparisons between races, we performed multivariable adjustments for age, gender, BP, and body mass index (BMI) a multiple linear regression model. Data reported are mean ±standard deviation. Results: 86 participants recruited from Birmingham, AL were included in the analysis. Participants had a mean age of 28.5±6.9 years, 36% were female, 41% were African Americans (AAs), and the mean BMI was 29.2±6.8 kg/m 2 . The mean sUA was 5.9±1.2 mg/dL (n=77, range: 3.9 to 8.5 mg/dL). We found a significantly lower sUA for African Americans compared to persons of other races (5.4±1.2 mg/dL vs 6.2±1.1 mg/dL, p=0.005). After multivariable analysis the difference in sUA between AAs and other races was attenuated to non-significance (p=0.33) due to the effects of BMI and gender. As expected, the association between sUA and gender was significant (Table). Conclusions: In this cross-sectional analysis of young adults, AAs had lower sUA concentrations than other races. However, this difference is explained by the effect of gender differences in sUA and BMI. A potential limitation is that participants were enrolled after they met a sUA threshold so not all the ranges of sUA in a normal population are represented in this analysis. Larger studies will be needed to fully address this question. References: Feig, D.I., JAMA, 2008. 300(8): p. 924–32. Fang, J. JAMA, 2000. 283(18): p. 2404–10. Gaffo, A.L. Arthritis Res Ther. 2012 Jan 6; 14(1):R4. Acknowledgements: National Institute of Arthritis and Musculoskeletal and Skin Diseases P50AR060772, K24AR052361 (to KGS). Disclosure of Interest: M. Saddekni: None declared, A. Gaffo Grant/research support from: Amgen, AstraZeneca, Consultant for: Cymabay, Ardea, Employee of: US Government, P. Foster: None declared, S. Biggers: None declared, E. Rahn: None declared, P. Li: None declared, K. Saag Grant/research support from: AstraZeneca, Crealta, Takeda, Consultant for: Ardea/AstraZeneca, Crealta, Takeda